Association between polymorphisms in the DNA repair genes, XRCC1, APE1, and XPD and acute side effects of radiotherapy in breast cancer patients - Chang-Claude, Jenny; Popanda, Odilia; Tan, Xiang-Lin; Kropp, Silke; Helmbold, Irmgard; Fournier, Dietrich von; Haase, Wulf; Sautter-Bihl, Marie-Luise; Wenz, Frederik; Schmezer, Peter; Ambrosone, Christine (Clinical cancer research, 2005)
Purpose: Several DNA repair gene polymorphisms have been described, which affect DNA repair capacity and modulate cancer susceptibility. We evaluated the association of six polymorphisms in the DNA repair genes: XRCC1 (Arg(194) Trp, Arg(280)His, and Arg(399)GIn), APE1 (Asp(148)Glu), and XPD (Lys(751)Gln and Asp(312)Asn), with the risk of acute skin reactions following radiotherapy. Design: We conducted a prospective study of 446 female patients with breast cancer who received radiotherapy after breast-conserving surgery. Individual genetic polymorphisms were determined using melting point analysis of sequence-specific hybridization probes. The development of acute skin reactions (moist desquamation) associated with DNA repair gene polymorphisms was modeled using Cox proportional hazards, accounting for cumulative biologically effective radiation dose. Results: Overall, the development of acute toxicity, which presented in 77 patients, was not associated with the genetic variants studied, although the hazard ratios (HR) were generally below 1. Risks were however differential by body mass index. Among normal-weight patients only, both carriers of theAPE1 (148)Glu and the XRCC1 (399)Gln alleles had decreased risk of acute skin reactions after radiotherapy (HR, 0.49 and 0.51, respectively). The results for XRCC1 were confirmed by haplotype analysis. When considering joint effects, we observed that compared with homozygote carriers of the wild-type allele in both genes, the risk was most strongly reduced in carriers of both APE1 (148)Glu and XRCC1 (399)GIn alleles with normal weight [HR, 0.19; 95% confidence interval (95% CI), 0.06-0.56] but not in those with overweight (HR, 1.39; 95% CI, 0.56-3.45; P-interaction = 0-009). Conclusion: The XRCC1 (399)Gln or APE1 (148)Glu alleles may be protective against the development of acute side effects after radiotherapy in patients with normal weight.